Potential and Accuracy of Hand Length and Hand Breadth in Sex Determination: An Insight into Hausa Population of Nigeria - Magaji G. Taura; Lawan H. Adamu; Abdullahi Y. Asuku; Kabiru B. Umar; Musa Abubakar; Isyaku I. Kibiya; Abdulrashid Sunusi (Arab Journal of Forensic Sciences & Forensic Medicine, 2020)
The identification of an individual in mass disasters and traffic accidents is a fundamental goal in forensic investigations. However, it is suggested that every population needs anthropological reference data. The objectives of this study were to determine the potential and accuracy of hand length and hand breadth in sex determination among the Hausa population of Nigeria. Random sampling was employed to select 204 male and 194 female subjects aged 18-30 years. Hand length and hand breadth were measured using standard protocols. Two-sample t-test, binary logistic regression, receiver operating characteristics curve, and Youden’s index were used for determining sex using hand dimensions. Posterior probability and likelihood ratio were used to determine the favor odds of each category of hand dimension in sex discrimination. A significant sexual dimorphism was observed in hand length and hand breadth with higher mean values in males. The variance of sex explained by hand parameters ranges from 38.50/51.35% (lower/upper limits) to 52.98/70.66%, which were exhibited by right hand length and left hand breadth respectively. The overall prediction and percentage accuracy of sex discrimination ranges between 80.40 to 86.70 % that were exhibited by right hand length and handbreadth respectively. We observed that left hand breadth exhibited higher Younden’s index with an area under curve (AUC) ranging from 91.60% to 96.05%. We found that hand length of > 189.99 mm was indicative of male origin and hand breadth of > 79.99 mm was indicative of male origin.